Estrategias pedagógicas para desarrollar y fortalecer la comprensión lectora en los estudiantes de grado segundo de primaria (2017)
This research is about how to design and apply different pedagogical strategies to help the strengthening and development of the Departmental Educative Institution RHIDA second graders reading comprehension of La Vega Cundinamarca, taking into account the implementing activities that generate interest and recognize the importance of reading in academic results, formation of reading habits keeping in mind children interests and the transformation and improvement of the teacher craft. To do this, a qualitative research was undertaken under the methodology of action research, using as instruments to collect information: field journals of the participating observer and non-participating observer, focal groups at the end of each programmed cycles (Three totally) and the final works of the students. The data was transcribed, categorized and triangulated for its analysis...